Stimulation of IL-8 release from epithelial cells by gas cooker PM10: a pilot study. Issue 3 (1st March 2001) - Dick, C A J; Dennekamp, M; Howarth, S; Cherrie, J W; Seaton, A; Donaldson, K; Stone, V
Abstract : OBJECTIVE: To measure the effect of matter collected by a method that has a 50% efficiency for particles with an aerodynamic diameter of 10 μm (PM10 ), generated by gas and electric cooking, on A549 epithelial cells with and without nitrogen dioxide (NO2 ). METHOD: Multiple indoor PM10 samples were collected on Teflon filters during the use of gas or electric cookers. Interleukin-8 (IL-8) concentrations were measured with a sandwich enzyme linked immunosorbent assay (ELISA) system. RESULTS: Treatment of A549 cells with PM10 generated from gas cooking resulted in increased concentrations of IL-8 compared with untreated cells; particles from the electric cooker had no effect. NO2 did not alter the concentration of IL-8. CONCLUSION: PM10 generated by gas cooking has the potential to cause proinflammatory effects in lung cells. This may have implications for susceptible people.